PENGGUNAAN CHATGPT PADA PROSES PEMBELAJARAN PADA MATA KULIAH PEMASARAN DIGITAL UNTUK MENINGKATKAN KEMANDIRIAN MAHASISWA DI STMA TRISAKTI - Sidik, Syahrial; Wahyuari, Wahyuari; Laratmase, Antonia Junianty; Suhendar, Bagus (P3M Trisakti School of Insurance (TSI), 2024)
New technologies, like ChatGPT, are changing the way we learn in school. Some people really like it, but others don't like it as much. Many people are talking about how ChatGPT affects education. The purpose of this study is to examine how the use of ChatGPT in the learning process can increase student independence at STMA Trisakti. This is really important because students are one of the people who use ChatGPT. The type of research used is descriptive-quantitative. The sample used is the pre-test and post-test results of all STMA Trisakti students in digital marketing courses, totaling 34 respondents. The data analysis techniques used in the study were a validity test, a reliability test, a prerequisite test, and a hypothesis test (a paired sample test) to see which one had the biggest increase. The results showed that there was a significant difference between the pre-test and post-test scores on whether the use of Chat GPT in the learning process can increase student independence at STMA Trisakti. These results can be used to conclude that the knowledge score in the learning process increases student independence at Stma Trisakti.